(untitled) (Global Journal of Medical Research, 2021)
Leukocytes are white blood cells that are specialised in initiating an immune response against pathogens. There are several types of leukocytes in the human body with various functions; also, leukocytes can be found in different parts of the body, protecting against pathogens. In the male reproductive system, leukocytes can be detected through many methods, and it has been shown the effectiveness of those leukocytes in defending the reproductive system. Yet, the high level of leukocytes can generate reactive oxygen species that can harm the sperms. Moreover, a high level of leukocytes can lead to a condition called leukocytospermia, which can point to low fertilisation, pregnancy and embryo development rate. Accordingly, this article will discuss the potential harm of high leukocytes level, in addition to the management and treatment of leukocytospermia.